Tantangan dan Peluang Jurnalisme di Era Kecerdasan Buatan: Studi Fenomenologi pada Jurnalis di TribunGorontalo.com - Yanter, Qori'ah; Sumarjo; Mursalim, Muhammad Akram (JAMBURA JURNAL ILMU KOMUNIKASI, 2025)
The advancement of artificial intelligence (AI) technology has brought significant changes to journalistic practices, including at local media outlets such as TribunGorontalo.com. This study aimed to identify the challenges and opportunities faced by joumalists in applying AI in the newsroom. The rescarch employed a qualitative phenomenological approach and used technological determinism theory as its theoretical foundation, utilizing in-depth interviews and observations. The findings reveal that key challenge sinclude data bias due to algorithm limitations, ethical dilemmas in maintaining originality and information accuracy, Al's limited ability to understand social context, and concerns about threats to the journalism profession. On the other hand, the opportunities offered include improved time efficiency, data automation, faster fact-checking, and replacement, that strengthens journalists 'performance in delivering relevant and accurate information. This study provides new perspectives on how local media adapt to AI technologies and emphasizes the importance of wise editorial policies and ethical awareness in optimizing Al use in joumnalistic practice.